HOW REPRESENTATIVE ARE PATIENTS WHO ACCESS THE MARIE CURIE NURSING SERVICE OF THE POPULATION OF PEOPLE WHO DIE EACH YEAR IN ENGLAND?. Issue 1 (1st March 2013) - Georghiou, T; Cooke, M; Bardsley, M
Abstract : Introduction: The Marie Curie Nursing Service (MCNS) provides nursing care and support to around 28 000 people at the end of life in their own homes each year. Aims and Methods: This study aimed to explore the extent to which MCNS patients are representative of all people at the end of life. Following approval from the National Information Governing Board and pseudonymisation of datasets, service data for 29 000 MCNS patients who received care between January 2009 and November 2011 were linked to NHS data on patient characteristics and hospital usage. A comparison group comprised 870 000 people who died during the same timeframe but did not receive MCNS care. Results: Multivariate analyses explored the extent to which the groups differed on demographic measures including age, gender, ethnicity and deprivation. Further analyses explored the differences in clinical variables including diagnoses and number of long term conditions. MCNS patients were much more likely to have a cancer diagnosis, and are considerably less likely to have a dementia diagnosis. Conclusions: The largest differences between MCNS patients and the population of people who die each year in England are in diagnostic variables, including cancer history. Multivariate analyses enable a meaningful comparison between the groups of variables of interest (eg, age), accounting for other factors known to be related to that variable (eg, cancer history).